Exercise in Antiquity and Modern Times: Catholicon for Healthy . Living (2019)
Ancient physicians such as Herodicus, Hippocrates and Galen recommended exercises as panacea for healthy living in antiquity. Modern scholars such as Christos and Tipton have variously demonstrated the importance of exercises and sports in ancient and modem European societies citing exercises as treatments for some illnesses by the doctor in the Hippocratic Corpus. This paper examined the importance of exercise in antiquity and modernity, even as it serves as a catholicon for healthy living, with a view to identifying the values and relevance of exercise in dealing with illnesses and promoting good health. Sallis and Owen behavioural epidemiology was adopted as theoretical framework. The historical and comparative methodologies were adopted as the study examined the historical trajectory and cross-cultural variations of exercise in antiquity and today’s world. The discourse in this study demonstrated that exercise has been functional as medicine and for healthy living in antiquity and modernity. Medical practitioners, exercise physiologists, including laymen understand its importance and further recommend exercise suitable for people of varying ages. Further studies may be designed to examine low to medium and medium to high intensity exercise and its health implications.